The Legal Politics of The Governor's Authority in the Formation of Regulatory Regulations of The Region/Municipal Head - Wijaya, Ruddy; Febrian; Ridwan; Apriandi, Mada (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study aims to analyze legal politics related to the authority of the governor in the formation of district / city head regulations. Legal policy is an important concept in understanding how power and law interact and influence the legislative process at the regional level. The authority of the governor as the representative of the central government in the region has significant implications for regional autonomy and the dynamics of the relationship between the provincial government and the district / city government. This research uses normative juridical method with statutory approach and conceptual analysis. The results show that the governor's authority in the formation of district / city head regulations often causes conflicts between central and regional interests. Political, economic, and social factors influence the governor's decision to approve or reject regulations proposed by district/city heads. In addition, it was found that there is vagueness and inconsistency in the regulations governing the governor's authority, resulting in legal uncertainty. The conclusion of this study emphasizes the importance of legal reforms that can clarify the limits of the governor's authority and increase transparency and accountability in the process of forming local regulations. Thus, it is expected to create harmonization between central and regional interests in order to realize good governance.Keywords:Legal Politics, Governor's Authority, Regional Head Regulation